Supporting young people at risk of school exclusion through Acceptance and Commitment Therapy (ACT) and allied models: A new service model and case study example - Cogan, Owen; Gillard, Duncan; Anderson, Ben; Hopkins, Sophie; Hulson-Jones, Amy; Hughes, Carl (Educational and child psychology, 2025)
Recent UK Government figures show that permanent exclusions and suspensions in England are increasing. Children with special educational needs (SEN), especially those with a primary need in the area of Social, Emotional and Mental Health (SEMH), are particularly vulnerable in this regard . Given the clear links between school exclusions and a wide range of negative life-outcomes – such as increased vulnerability to criminality and prison sentences – the need to find creative and innovative ways of reducing exclusions and suspensions is a clear and present priority. This paper presents a new, outcomes-based Educational Psychology (EP) service delivery model for children, families and schools, rooted in Acceptance & Commitment Therapy and related models derived from the world of Contextual Behavioural Science (CBS). The paper also presents a case study example, including intervention outcomes and processes, to illustrate how this new service delivery model takes a whole-child, contextual, person-centred and evidence-informed approach, to help create the conditions for a young person to thrive and be more fully included within mainstream education.